MicroRNA-26a-3p rescues depression-like behaviors in male rats via preventing hippocampal neuronal anomalies - Li, Ye; Fan, Cuiqin; Wang, Liyan; Lan, Tian; Gao, Rui; Wang, Wenjing; Yu, Shu Yan (The Journal of Clinical Investigation, 2021)
Depression is a neuropsychiatric disease associated with neuronal anomalies within specific brain regions. In the present study, we screened microRNA (miRNA) expression profiles in the dentate gyrus (DG) of the hippocampus and found that miR-26a-3p was markedly downregulated in a rat model of depression, whereas upregulation of miR-26a-3p within DG regions rescued the neuronal deterioration and depression-like phenotypes resulting from stress exposure, effects that appear to be mediated by the PTEN pathway. The knockdown of miR-26a-3p in DG regions of normal control rats induced depression-like behaviors, effects that were accompanied by activation of the PTEN/PI3K/Akt signaling pathway and neuronal deterioration via suppression of autophagy, impairments in synaptic plasticity, and promotion of neuronal apoptosis. In conclusion, these results suggest that miR-26a-3p deficits within the hippocampal DG mediated the neuronal anomalies contributing to the display of depression-like behaviors. This miRNA may serve as a potential therapeutic target for the treatment of depression.